The enigmatic Triassic ovulate reproductive structures of Dordrechtites are recurved cupules fundamentally comparable to the cupules of Doylea and similar plants - Crane, Peter R (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.